Older People, Town Centres and the Revival of the 'High Street'. (1st January 2021) - Phillips, Judith; Walford, Nigel; Hockey, Ann; Sparks, Leigh
ABSTRACT: Concern for the future of town centres and their retail cores, the 'high street', is not new. Responses to this have often been somewhat one dimensional, focusing on their role as places of consumption, employment, leisure and heritage. We consider the potential multiple roles of older people in helping revive and rejuvenate town centres given the centrality of place for healthy supportive living, community and social participation and 'ageing in place'. Taking an environmental gerontology perspective, we ask whether the WHO age friendly cities/communities' framework should be considered further in approaches to reviving town centres in a post-Covid-19 world.